Probe-based confocal laser endomicroscopy in the diagnosis of diffuse cystic lung disease in Sjögren’s syndrome - Mamenko, Igor Sergeevich; Vasilev, Igor V.; Simonov, Roman V.; Zakharova, Anna S.; Gavrilov, Pavel V.; Dvorakovskaya, Ivetta V.; Novitskaya, Tatiana A.; Yablonskiy, Petr K. (Monaldi Archives for Chest Disease, 2023)
Sjögren’s syndrome is a systemic autoimmune disease characterized by lymphocytic infiltration of various organs with a wide frequency of pulmonary involvement. Diffuse cystic lung disease in Sjögren’s syndrome is a rare condition and requires differential diagnosis with other cystic pathologies such as lymphangioleyomiomatosis or Langerhans cell histiocytosis. Probe-based confocal laser endomicroscopy (pCLE) is a method of in vivo investigation of airways and lung tissue at a microscopic level during bronchoscopy. We used this method in diffuse cystic lung disease caused by Sjögren’s syndrome. The pCLE image showed a large number of fluorescent cells, presumably lymphocytes, in bronchioles, dilated alveolar spaces with fluid, and thin alveolar walls. We think that the presence of the bronchiolar cell pattern can be used to differentiate between the pulmonary manifestations of Sjögren’s disease and other cystic lung diseases.